Implementation of marriage itsbat in Aceh - Aulia Mubarak; M. Adli; Iman Jauhari (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2021)
This paper describes the process of marriage itsbat in Aceh and its approval factors despite its non-compliance with the applicable provisions. From the study results, it is known that the judge determining marriage itsbat prioritized benefit (maslahah) for the litigants. Its approval is considered to have more positive impacts, both for the litigants and their children. When it is granted, their marriage has had legal force and is recognized by the state, with the result that the litigants and their children have the same rights as those who register their marriage. This study used empirical legal research method obtained by conducting interviews. For further suggestion, it is expected that the government give legal socialization to increase public awareness of the importance of marriage registration